2007
DOI: 10.1021/om700583q
|View full text |Cite
|
Sign up to set email alerts
|

Investigations Directed at Catalytic Carbon−Carbon and Carbon−Oxygen Bond Formation via C−H Bond Activation

Abstract: A potential catalytic cycle for the formation of new C-C and C-O linkages from hydrocarbon feedstocks and readily available olefin and ketone substrates mediated by Cp′M(NO)(L) (M ) Mo, W; Cp′ ) Cp*, Cp; L ) Lewis base) fragments has been investigated. The cycle is based on three steps: (1) oxidative addition of the hydrocarbon substrate to the metal center, (2) subsequent hydrometalation of the olefin or the ketone, and (3) final reductive elimination of the coupled product. Of the various Cp′M-(NO)(L) groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Similarly, reaction of 3 with styrene gives the hydrido vinylsilyl complex 5 (Scheme 3), which probably emerges from styrene coupling with the silanimine intermediate D (Scheme 2), followed by C À H activation in the CH 2 CHPh fragment. Similar alkene insertion into a Zr À Si bond has been observed previously by Surprisingly, NMR experiments indicated that reactions of 3 with acetone and acetophenone lead to the selective formation of the ketone complexes 6 [17] and 7, [18] respectively, accompanied by the evolution of one equivalent of PhSiH 3 and the formation of a difficult-to-characterize mixture of volatile silicon-containing compounds (Scheme 3). All attempts to trace the fate of the extruded silylene fragment…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Similarly, reaction of 3 with styrene gives the hydrido vinylsilyl complex 5 (Scheme 3), which probably emerges from styrene coupling with the silanimine intermediate D (Scheme 2), followed by C À H activation in the CH 2 CHPh fragment. Similar alkene insertion into a Zr À Si bond has been observed previously by Surprisingly, NMR experiments indicated that reactions of 3 with acetone and acetophenone lead to the selective formation of the ketone complexes 6 [17] and 7, [18] respectively, accompanied by the evolution of one equivalent of PhSiH 3 and the formation of a difficult-to-characterize mixture of volatile silicon-containing compounds (Scheme 3). All attempts to trace the fate of the extruded silylene fragment…”
supporting
confidence: 74%
“…[18] As for ketones, the reaction of (ArN) 2 Mo(PMe 3 ) 3 with benzaldehyde gives an h 2 complex (8), characterized by an up-field C À H signal at d = 5.69 ppm in its 1 H NMR spectrum. [17] These observations suggest that in the hydrosylation of carbonyl compounds the active catalyst is probably formed from 3 after silane elimination, but before silylene extrusion from D.…”
mentioning
confidence: 96%
“…The formulation of complex 24 as an η 2 adduct is further supported by the appearance of red‐shifted CO stretches in the IR spectrum (1596 and 1487 cm −1 versus 1720 cm −1 for the free PhHCO) 11ac,e. 50, 51 Complex 24 is unstable under vacuum; however, cooling the reaction mixture down to −30 °C allowed us to crystallize complex 24 in its analytically pure form. Alternatively, a mixture of complexes 23 and 24 can be obtained through a transfer hydrogenation reaction of benzaldehyde with isopropoxy derivative 18 (Scheme ).…”
Section: Resultsmentioning
confidence: 86%
“…However, the 31 P{ 1 H} NMR spectrum at −60 °C shows two doublets ( 2 J (P,P)=218.7 Hz) at δ =8.0 and 6.4 ppm for two nonequivalent trans‐ PMe 3 ligands. In the 1 H NMR spectrum, the carbonyl protons of two η 2 ‐benzaldehyde ligands appear as broad, upfield‐shifted signals at δ =5.42 (br s) and 5.18 ppm (br d, J (H,P)=9.6 Hz),51 that are coupled in the 1 H 13 C HSQC spectrum to the carbonyl carbon atoms at δ =85.2 and 86.1 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation